Efficient single copy integration via homology-directed repair (scHDR) by 5′modification of large DNA donor fragments in mice - Medert, Rebekka; Thumberger, Thomas; Tavhelidse-Suck, Tinatini; Hub, Tobias; Kellner, Tanja; Oguchi, Yoko; Dlugosz, Sascha; Zimmermann, Frank; Wittbrodt, Joachim; Freichel, Marc (Nucleic acids research, 2023)
CRISPR/Cas-based approaches have largely replaced conventional gene targeting strategies. However, homology-directed repair (HDR) in the mouse genome is not very efficient, and precisely inserting longer sequences using HDR remains challenging given that donor constructs preferentially integrate as concatemers. Here, we showed that injecting 5′ biotinylated donor DNA into mouse embryos at the two-cell stage led to efficient single-copy HDR (scHDR) allele generation. Our dedicated genotyping strategy showed that these alleles occurred with frequencies of 19%, 20%, and 26% at three independent gene loci, indicating that scHDR was dramatically increased by 5′ biotinylation. Thus, we suggest that the combination of a 5′ biotinylated donor and diligent analysis of concatemer integration are prerequisites for efficiently and reliably generating conditional alleles or other large fragment knock-ins in the mouse genome.
Online veröffentlicht: 19. Dezember 2022
Gesehen am 26.02.2024